Implementing Contextual Teaching and Learning Models in Islamic Religious Education Learning - Ulum, Bakhrul; Syafi'i, Imam (Academicus: Journal of Teaching and Learning, 2022)
The purpose of this article was to analyze the planning, implementation, and supporting and inhibiting factors in the implementation of the Contextual Teaching and Learning (CTL) learning model in PAI learning at Bakalan Elementary School, Pasuruan City. This research used descriptive qualitative research. Data collection techniques used in this study were interviews, observation, and documentation. In data analysis, the researcher used a qualitative data analysis approach. Validation of data using triangulation, implication, and peer correction. The substantive findings of the Implementation of Contextual Teaching and Learning (CTL) Learning Models in PAI Learning at Bakalan Elementary School Pasuruan are that: 1) Learning planning carried out by compiling learning tools will be more effective if it starts through the plan to lesson and lesson to plan activities. Lessons to plan activities are used as a reflection of the PAI learning process that has been implemented in class IV. 2) Implementation of the Contextual Teaching and Learning (CTL) Learning Model in PAI Learning at Bakalan State Elementary School Pasuruan includes the Requirements for the Implementation of the Learning Process (which explains learning groups, the minimum workload of PAI teachers, textbooks, classroom management), Implementation of Learning (which explaining the Final Activity), Assessment (explaining attitude assessment, skill assessment, knowledge assessment).